SOME RESULTS OF GENERALIZED LEFT (Î¸,Î¸)-DERIVATIONS ON SEMIPRIME RINGS (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Let R be an associative ring with center Z(R) . In this paper , we study the commutativity of semiprime rings under certain conditions , it comes through introduce the definition of generalized left(Î¸,Î¸)- derivation associated with left (Î¸,Î¸) -derivation , where Î¸ is a mapping on R .